ANALYSIS OF DIFFICULTY LEVEL OF PHYSICS NATIONAL EXAMINATIONâS QUESTIONS - Yusrizal, Yusrizal (Jurnal Pendidikan IPA Indonesia, 2016)
This study aimed to determine: (1) the difficulty level of items in physics National Exam of 2013 (2) physics materials that were difficult and very difficult. The subjects were all students of science major in third gradeat SMAN Banda Aceh in the academic year of 2013/2014. The samples were 10 randomly selected senior high schools. The data were obtained through analyzing the answers of physics National Examin 2013. The results showed that (1) the high school students in Banda Aceh experienced difficult and very difficult level questions to be answer in the 2013 exam, (2) thedifficult materials were: free fall, the potential energy and series of obstacles. The very difficult materials were: the rotational motion, motion and force on the pulley, effort, fluid, sound intensity, transformer, atomic theory, quantum theory, relativity, fusion and radio isotopes.